(untitled) (Comprehensive Journal of Science, 2024)
The present paper deals with classification of oilfield water of Maraghand Amal formations at Amal oil field, concession NC-12 ,in the eastern margin of the Sirt basin, Libya.Ten chemically analyzed water samples from different wells were used in this study; chemical analyses of the major ions of the water samples showed Total Dissolved Solids (TDS) in the ranges from 205487 to 234912mg/l. The geochemical ratios of Na/Cl, ((Na-Cl)/SO4), and ((Cl-Na)/Mg) were calculated for formation water of ten wells classification following Sulin’s (1946), whereindicate that all of these water are Cl-Ca type waters under subsurface conditions; this type reflects isolated waters with hydrostatic conditions.According to Bojarski’s (1970), the chloride-calcium type of this water subdivided to chloride-calcium III, which reflects the favorable zone for the preservation of hydrocarbons, followed by chloride-calcium II in other wells.This class reflects the transition zone between active hydrodynamic and stable zones. Graphical methods in water analysis enable efficient pattern comparison for quick identification of differences between water samples.Consequently, both the piper diagram and the stiff diagram were utilized in this study. The piper diagram in this study indicates most of the samples were classified as (Na++K+) and Ca2+ types of cations and Cl- types of anions;then these waters consist of the alkalis that exceed alkaline earths.The Stiff Diagram polygons showed most of the samples reveals similar chemical compositions with high chlorine and sodium levels, followed by magnesium and bicarbonate, while sulfate is low. In contrast, the waters in some wells have higher magnesium concentrations.